Exercise physiology of the left atrium: quantity and timing of contribution to cardiac output - Bhatt, Anish; Flink, Laura; Lu, Dai-Yin; Fang, Qizhi; Bibby, Dwight; Schiller, Nelson B. (American journal of physiology. Heart and circulatory physiology, 2021)
Diseases of the left atrium (LA) are major sources of disability (e.g., strokes and fatigue), but its exercise physiology has been unstudied. Such knowledge may allow early recognition of disease and suggest therapies. We show that in normal subjects, low-level exercise decreases LA volume and increases its ejection fraction. However, these changes offset each other volumetrically, and the contribution to LV filling from a full to an empty LA (reservoir function) is static. Higher levels of exercise do not change LA reservoir contribution. Blood flowing directly from the pulmonary vein to LV (conduit flow) impelled by augmented LV active relaxation (suction) is the major source of a modest increase in LV stroke volume. The major source of increased cardiac output with exercise is heart rate. During all stages of exercise, the LA works hard but only to keep up. We believe that our findings provide an additional set of benchmarks through which to quantitate LA pathology and gauge its progression. Although the phases of left atrial (LA) function at rest have been studied, the physiological response of the LA to exercise is undefined. This study defines the exercise behavior of the normal left atrium by quantitating its volumetric response to graded effort. Healthy subjects ( n = 131) were enrolled from the Health eHeart cohort. Echocardiograms were obtained at baseline and during ramped supine bicycle exercise. Left ventricular volume index, stroke volume index (LVSVI), left atrial end-systolic volume index (LAESVI), left atrial end-diastolic volume index (LAEDVI), and left atrial emptying fraction (LAEF), reservoir fraction, and conduit fraction were analyzed. The LVSVI increased with low exercise but did not increase further with peak exercise; cardiac output increased through the agency of heart rate. The LAESVI and LAEDVI decreased and the LAEF increased with exercise. As a result, the LA reservoir volume index was static throughout exercise. The reservoir fraction decreased from 46% at rest to 40% with low exercise ( P < 0.001) in association with increased LVSVI and remained similar at peak exercise. The conduit volume index increased from 20 mL/m 2 at rest to 24 mL/m 2 at low exercise and stayed the same at peak exercise. Similarly, the conduit fraction increased from 54% at rest to 60% at low exercise ( P < 0.001) and did not change further with peak exercise. Although atrial function increased with exercise, the major contribution to the augmentation of LV stroke volume is LA conduit fraction, a marker of active ventricular relaxation. Furthermore, the major determinant of raising cardiac output during high-level exercise is heart rate. NEW & NOTEWORTHY Diseases of the left atrium (LA) are major sources of disability (e.g., strokes and fatigue), but its exercise physiology has been unstudied. Such knowledge may allow early recognition of disease and suggest therapies. We show that in normal subjects, low-level exercise decreases LA volume and increases its ejection fraction. However, these changes offset each other volumetrically, and the contribution to LV filling from a full to an empty LA (reservoir function) is static. Higher levels of exercise do not change LA reservoir contribution. Blood flowing directly from the pulmonary vein to LV (conduit flow) impelled by augmented LV active relaxation (suction) is the major source of a modest increase in LV stroke volume. The major source of increased cardiac output with exercise is heart rate. During all stages of exercise, the LA works hard but only to keep up. We believe that our findings provide an additional set of benchmarks through which to quantitate LA pathology and gauge its progression.